Role of State and Foreign Ownership and Dividend Policy: Supply Chain Strategies in Emerging Market Perspective - Al-dulemy, Haidar Hamza Jody (ExcelingTech, 2019)
This investigation is aimed to shed light on the relationship between dividend policy and ownership structure based on the supply chain strategy in the emerging markets. This study hypothesizes the concept that concentrated foreign ownership have different dividend policy as compared to state-owned companies. Moreover, state ownership is also examined with respect to dividend policy. The phenomenon is explored by using a panel data of 2001 to 2015 of companies listed in Iraqi stock exchange. A strong impact of ownership structure was noticed in dividend policy. Companies with higher government ownership are more tilted to pay cash dividends and create tunneling effect. However, foreign ownership concentrated firms are more likely to pay stock dividends. Further, firms with growth opportunities are likely to pay stock dividends while the negative relationship with growth and cash dividend was noticed. This study has significant policy guidelines for investors, managers and academics. The findings of this study are also significant from emerging market perspective.